Alfabetização na conteporaneidade: um estudo das concepções teóricas mais difundidas no Brasil nas últimas décadas - SANTOS, Jheovanda de Almeida (2022)
Considering that literacy plays an extremely important role in the social life of any human being, this study aims to map the theoretical approaches to literacy that have been most widely circulated in the Brazilian academic and educational context since the 1980s and to analyze the approximations and distances existing between them. Thus, the methodology adopted in the research was based on a bibliographic and exploratory analysis, based on reference authors for the discussion of the theme. Thus, the study is based on Soares (2018, 2002); Friar (2007); Mortatti (2006); Ferreiro and Teberosky (1986); Smolka (2018); Andrade (2017); Kleiman (2002); Tfouni (2006); Goulart (2006); Red (2009); Carvalho (2010). From the analysis of bibliographic data, we identified similarities and differences between the concepts of literacy discussed, as well as the understanding of learning to read and write inherent to each of them.